Good Faith Principle dalam Hukum Perjanjian: Perspektif Hukum Islam - Ambarwati, Auliah; Anggraeniko, Litya Surisdani (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2025)
The Good Faith Principle is one of the fundamental principles in Contract Law according to Civil Law scholarship, as stipulated in the Civil Code (Kitab Undang-undang Hukum Perdata) that every agreement (contract) must be executed in good faith. This principle itself has been extensively studied with various interpretations regarding the meaning of the good faith principle. This paper aims to examine the conception of the Good Faith Principle in Contract Law from an Islamic perspective, which subsequently reveals that first, in various verses of the Quran and in the Hadith, there are prohibitions against acts containing bad faith, which means violating the principle of good faith; second, that good faith is a reflection of one's piety. A person who acknowledges themselves as a Muslim and believes in the matters prescribed in the Quran and Hadith is on a path to attaining happiness, which is the ultimate goal of a Muslim